Efficient exact pattern-matching in proteomic sequences - Deusdado, Sérgio (2011)
This paper proposes a novel algorithm for complete exact pattern-matching focusing the specificities of protein sequences (alphabet of 20 symbols) but, also highly efficient considering larger alphabets. The searching strategy uses large search windows allowing multiple alignments per iteration. A new filtering heuristic, named compatibility rule, contributed decisively to the efficiency improvement. The new algorithm’s performance is, on average, superior in comparison with its best-rated competitors.